Uexküll’s Surroundings - Schnödl, Gottfried; Sprenger, Florian (2022)
With its diversity of possible Umwelten or environments for living things, Jakob von Uexküll’s Umwelt theory has been hailed by many readers as the first step toward an innovative, pluralistic conception of nonhuman life. But what is generally ignored is its structural conservatism, its identitarian logic in which everything should remain in its place and nothing should mix, and its proximity to Nazi ideology and politics. By turning the spotlight on these neglected aspects, Uexküll’s Surroundings opens up a new perspective on Uexküll’s Umwelt theory.